Efficacy of Continuous Dosing of Tadalafil Once Daily vs Tadalafil On Demand in Clinical Subgroups of Men with Erectile Dysfunction: A Descriptive Comparison Using the Integrated Tadalafil Databases. Issue 5 (1st May 2016) - Brock, Gerald; Ni, Xiao; Oelke, Matthias; Mulhall, John; Rosenberg, Matt; Seftel, Allen; D'Souza, Deborah; Barry, Jane
ABSTRACT: Introduction: Various factors play a role in the development of erectile dysfunction (ED). Aim: To provide a descriptive comparison of erectile function response for tadalafil on-demand (PRN) and once-daily (OAD) dosing regimens in patients with common comorbid conditions, treatments, or risk factors that can be considered when treating ED. Methods: In total, 17 PRN and 4 OAD placebo-controlled studies were included in the integrated database in these pooled analyses. Data were analyzed from patients treated with placebo, tadalafil 10 mg (low dose), and 20 mg (high dose) for the PRN studies and placebo, tadalafil 2.5 mg (low dose), and 5 mg (high dose) for the OAD studies. Main Outcome Measures: The effects of tadalafil were measured using the International Index of Erectile Function administered from baseline to week 12. A descriptive comparison of the efficacy of tadalafil PRN vs OAD was examined in the clinical populations. Results: Baseline characteristics of 4, 354 men were comparable between the PRN and OAD groups, with differences seen only in the variables of race, body mass index (BMI) of at least 30 kg/m 2, and alcohol use. Tadalafil was efficacious at improving erectile function for all clinical populations, except for the low-dose OAD group, which demonstrated a weaker effect vs placebo than the high-dose OAD group, and the low- and high-dose PRN groups vs placebo for patients with BMI of at least 30 kg/m 2 for patients without a cardiovascular disorder, smokers, patients with ED duration shorter than 1 year, and patients without previous phosphodiesterase type 5 inhibitor use. Tadalafil was efficacious for patients with or without diabetes mellitus, arterial hypertension, hyperlipidemia, and alcohol use at baseline. Conclusion: Tadalafil OAD and PRN regimens showed efficacy in patients with ED. No clinical populations of patients with ED seemed to benefit overwhelmingly from one dose regimen over the other.